Embryonic development of the annual killifish Austrofundulus limnaeus: An emerging model for ecological and evolutionary developmental biology research and instruction. Issue 11 (8th May 2017) - Podrabsky, Jason E.; Riggs, Claire L.; Romney, Amie L.; Woll, S. Cody; Wagner, Josiah T.; Culpepper, Kristin M.; Cleaver, Timothy G.
Abstract : Background: Austrofundulus limnaeus is an annual killifish from the Maracaibo basin of Venezuela. Annual killifishes are unique among vertebrates in their ability to enter into a state of dormancy at up to three distinct developmental stages termed diapause I, II, and III. These embryos are tolerant of a wide variety of environmental stresses and develop relatively slowly compared with nonannual fishes.Results: These traits make them an excellent model for research on interactions between the genome and the environment during development, and an excellent choice for developmental biology laboratories. Furthermore, A. limnaeus is relatively easy to maintain in a laboratory setting and has a high fecundity, making it an excellent candidate as an emerging model for studies of development, and for defining the limits of developmental buffering in vertebrates.Conclusions: This study reports for the first time on the detailed development of A. limnaeus and provides a photographic and illustrated atlas of embryos on the two developmental trajectories possible in this species. Developmental Dynamics 246:779–801, 2017 . © 2017 Wiley Periodicals, Inc. Key Findings: Development of Austrofundulus limnaeus is described in detail with associated photographic images. The importance of studies that focus on the development of emerging model organisms is stressed.